SOCIAL UPHEAVALS IN KHUSHWANT SINGH’S TRAIN TO PAKISTAN - Linus Rumapea (Muse: Jurnal of Art, 2022)
This is a study of Khushwant Singh’s novel Train to Pakistan which is seen as the reflection of social upheavals.The novel shows that people of different religions live together peacefully, but they are divided into enmity groups who kill each other having provoked by some irresponsible actors. They spread hatred issues of accusation and conspiracy and persons of high position and power intentionally let situation become worse to get the benefit. Brotherhood, neighborhood, and friendship disappear replaced by prejudice, hatred, and enmity. Conspiracy and provocation are the sources of tragedy where deaths are vanity, and ruins are regretful. These are intolerable condition of humanity all people have to prevent to happen and to take lessons of what the novel reflects